Radiotherapy and chemotherapy in patients with primary invasive vaginal carcinoma - Blecharz, Paweł; Urbański, Krzysztof; Reinfuss, Marian; Szatkowski, Wiktor; Jasiówka, Marek (Contemporary Oncology/Współczesna Onkologia, 2010)
Methods of radiotherapy and chemotherapy for patients with primary invasive vaginal carcinoma (PIVC) are presented in the paper. Techniques of teleradiotherapy and intracavitary as well as interstitial brachytherapy are discussed. Optimal treatment volume, dose and fractionation schedules are defined. Principles of combining teleradiotherapy with brachytherapy, according to FIGO stages, are suggested. Special attention is paid to controversies concerning radiation dose calculation methods and radiobiological equivalent doses delivered from external beam radiotherapy and brachytherapy. The focus is also placed on toxicity and possible differences in treatment results in patients with PIVC, treated with LDR and HDR brachytherapy. The value of radiochemotherapy and palliative chemotherapy in this group of patients is analysed.